Pattern Recognition Models: A Study and Review - Jahagirdar, Alifiya; Pawar, Dr. Vrushsen (IJRDO -Journal of Computer Science Engineering, 2016)
Pattern recognition has become more popular in the coming years and it’s applied in the wider areas of research. The application areas spread into medicine, bioinformatics, data mining, speech recognition, handwriting recognition, face recognition, objects in satellite images and many others. In this paper we have reviewed methods used in pattern recognition. We will be studying different methods used for pattern recognition like statistical and structural techniques, template matching, neural network, fuzzy method and hybrid models.